Perancangan Ulang Hotel Grand Tjokro Premiere Bandung Dengan Pendekatan Lokalitas - Oktaviani, Windi; Laksitarini, Niken; Bayu Perdana, Aditya (Telkom University, 2024)
The hotel and restaurant industry plays a crucial role in Indonesia's tourism development, contributing around 60% of the revenue. Bandung, as one of the favorite tourist destinations, attracts visitors with its various attractions. The provision of star hotels in the city continues to increase, impacting industry competition. In 2017, there was a decrease in the number of non-star hotels due to many converting to boarding houses. It is important for hotels to develop by prioritizing customer satisfaction, including meeting expectations and creating satisfying experiences. Standards and definitions of hotels are regulated by the government to ensure quality services. One example of a hotel in Bandung is the Hotel Grand Tjokro Premiere Bandung, which has played a significant role in Bandung's tourism industry since its establishment in 2015. However, there are some shortcomings in implementing local values in the hotel's interior design and restaurant layout. Through redesign, it is hoped that this hotel can strengthen its local identity and enhance guest satisfaction, while remaining competitive in the Bandung hotel market. Keyword: Bandung, hotel bintang 4, locality